The Stability of a Generalized Tobin Model - Hadjimichalakis, Michael G.; Okuguchi, Koji (Review of Economic Studies, 1979)
Michael G. Hadjimichalakis, Koji Okuguchi; The Stability of a Generalized Tobin Model, The Review of Economic Studies, Volume 46, Issue 1, 1 January 1979,